Glycemic Control of Non-Hodgkin Lymphoma (NHL) Non-Diabetes Mellitus (DM) Patient in the First CHOP Chemotherapy (Medico Legal Update, 2021)
Non-Hodgkin’s lymphoma (NHL) chemotherapy is cyclophosphamide, doxorubicin, vincristine, andprednisone (CHOP) have hyperglycemia side effects that affect the success of chemotherapy. Improvedglycemic control decreases morbidity and mortality. Determine the glycemic control changes in non-DMNHL patients before and the sixth day after the first CHOP chemotherapy.Method: Prospective longitudinal observational analytic study in the Internal Medicine Inpatient Unit Dr.Soetomo Teaching Hospital Surabaya, involved all the first CHOP chemotherapy NHL patients duringNovember 2019-February 2020. A total of 21 patients met chemotherapy requirements and were not DM.The glycemic control check uses the hexokinase method and a glucometer (Easy Touch®). Data analysisusing the Wilcoxon test was considered significant if p